Tax Calculation for Productive Employees Based on Knowing the Net Salary: The Reversed Method - النائلي مصطفي (Dirasat in Economics and Business, 1982)
this paper presents a new method for calculating on a monthly net salary and the various payments that are received by productive employees by the Socialist Productive unite. The normal method for calculating tax duties usually starts with knowing the gross amount whose calculation is based on the income tax regulations. When the gross amount is known the case is analysed by using the normal method. But if the gross amount is not known, and the net amount is substituted instead then our problem originates. The main objective of this paper is to introduce a detailed method of duties calculation on reversed bases. The analysis starts with the net amount and is reversed until the gross amount is reached. By using this method we also will reach the necessary tax sub-calculations needed for the preparation of the employees' tax payments.